Retrospective analysis of the use of 22-gauge and 25-gauge needles for EUS-guided fine needle aspiration of solid lesions - Ogutmen Koc, Deniz; Gökden, Yasemin (Journal of Surgery and Medicine, 2021)
Background/Aim: Data on the comparison of diagnostic yields of 22-gauge (22G) and 25-gauge (25G) needles used in endoscopic ultrasound guided fine needle aspiration (EUS-FNA) biopsy usually include solid pancreatic masses. In our study, we compared the diagnostic yield, safety, and performance characteristics of 22G and 25G needles in the EUS-FNA of various solid lesions in or adjacent to the upper gastrointestinal wall and suspicious lymph nodes. Methods: In this retrospective cohort study, we enrolled patients who underwent EUS-FNA using 22G and 25G needles between August 2018 and January 2020. We compared EUS-FNA results with histological findings in operated patients and long-term clinical follow-up results in non-operated patients. Results: Seventy-nine patients (40 patients with 22G needles) were enrolled. There were pancreatic solid masses in 50 (63.3%) patients, subepithelial lesions in 13 (16.5%), suspicious lymph nodes in 12 (15.2%), and various lesions adjacent to the lumen in 4 (5.1%) patients. The diagnostic yield of 22G and 25G needles were 92.5% and 94.9%, respectively, which were similar (P=0.664). EUS-FNA of 2 pancreatic masses required a crossover from a 22G needle to a 25G needle due to lesion stiffness. The technical success rate for the lesion type was 100% and 95% for 25G and 22G needles, respectively (P=0.160). No major complications were observed with either needle. Conclusions: The 25G needle was not superior to the 22G needle in terms of diagnostic yield and safety profile in EUS-FNA of solid lesions. The use of 25G needles in hard masses can provide ease of puncture.